Enhancement of lightweight block cipher algorithms - Taha Alshaikhli, Imad Fakhri; Al-Dabbagh, Sufyan Salim Mahmood; Zaba, Muhammad Reza (IIUM Press, International Islamic University Malaysia, 2017)
This research dealt with three problems; First, it is difficult to optimized three factors at same time. Second, there are many researches still trying to find an algorithm that has the highest level of security. Third, there is lack knowledge on key dependent S-box within lightweight algorithms. All these problems solved in three directions. The first direction proposed lightweight block cipher algorithm called OLBCA (Optimized Lightweight Block Cipher Algorithm) that it outperformed PRESENT, which is one of the famous lightweight algorithm through three factors security, performance and cost. The results showed that OLBCA is more secure than PRESENT in terms of (differential cryptanalysis, integral cryptanalysis and boomerang attack). Also, the cost of OLBCA is less than PRESENT and the OLBCA is faster than PRESENT. The second direction proposed another lightweight block cipher algorithm called HISEC (Highest Security lightweight block cipher algorithm). The results showed that HISEC has the higher security than many existing lightweight algorithms especially in the resistance of (differential cryptanalysis, integral cryptanalysis and boomerang attack) while the cost of HISEC still reasonable. The third direction proposed five novel methods for generating key dependent S-box in lightweight block cipher algorithms and we did intensive analysis regarding to the security and cost. To the best of our knowledge, this is the first study that analyse the methods for generating key dependent S-box with lightweight block cipher algorithms.